Crime Prevention Strategy Of Terrorism Crime In Indonesia (Case Study In Sukoharjo) - Apromico Apromico; Eko Soponyono Soponyono; Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The terror makes rampant and perpetrators do not hesitate to hurt people even from officers and agents of Sukoharjo. This relates to the radical rapidly developing understanding and prevention that does not touch the grass roots. This study aims to analyze the characteristics of terrorism, prevention and radical ideal strategy to prevent terrorism. Juridical sociological research method is the specification of descriptive analytical research. The use of primary and secondary data by the method of collecting data through field studies and literature. Data analysis method used is qualitative analysis. Knives used analysis of development policy theory of criminal law, Theory of Rule of Law and Theory of Crime Prevention. The results of the study authors found the spread of radical terrorism as the entry of digital information technology so as to further spread of radical terrorists massively, Political Typology Limited was listed on terrorism, that terrorism is politics that characterized the approach of a revolutionary group, the motivation which are political or ideological. Formulation radical prevention of terrorism using national preparedness, counter-radicalization and de-radicalization. Ideal strategy terrorism prevention policies that have been implemented with the involvement of the institutions, the private sector and community groups whose influence on terrorism.Keywords: Strategy; Prevention; Terrorism; Sukoharjo.